Contribution of liquid, NAT and ice particles to chlorine activation and ozone depletion in Antarctic winter and spring - Kirner, O.; Müller, Rolf; Ruhnke, R.; Fischer, H. (Atmospheric Chemistry and Physics, 2015)
Heterogeneous reactions in the Antarctic stratosphere are the cause of chlorine activation and ozone depletion, but the relative roles of different types of polar stratospheric clouds (PSCs) in chlorine activation is an open question. We use multi-year simulations of the chemistry-climate model ECHAM5/MESSy for Atmospheric Chemistry (EMAC) to investigate the impact that the various types of PSCs have on Antarctic chlorine activation and ozone loss.One standard and three sensitivity EMAC simulations have been performed. In all simulations a Newtonian relaxation technique using the ERA-Interim reanalysis was applied to simulate realistic synoptic conditions. In the three sensitivity simulations, we only changed the heterogeneous chemistry on PSC particles by switching the chemistry on liquid, nitric acid trihydrate (NAT) and ice particles on and off. The results of these simulations show that the significance of heterogeneous reactions on NAT and ice particles for chlorine activation and ozone depletion in Antarctic winter and spring is small in comparison to the significance of heterogeneous reactions on liquid particles. Liquid particles alone are sufficient to activate almost all of the available chlorine, with the exception of the upper PSC regions between 10 and 30 hPa, where temporarily ice particles show a relevant contribution. Shortly after the first PSC occurrence, NAT particles contribute a small fraction to chlorine activation.Heterogeneous chemistry on liquid particles is responsible for more than 90% of the ozone depletion in Antarctic spring in the model simulations. In high southern latitudes, heterogeneous chemistry on ice particles causes only up to 5 DU of additional ozone depletion in the column and heterogeneous chemistry on NAT particles less than 0.5 DU.The simulated HNO3, ClO and O3 results agree closely with observations from the Microwave Limb Sounder (MLS) onboard NASA's Aura satellite.